THE IMPACT OF LEARNING MANAGEMENT SYSTEMS (LMS) ON STUDENT PERFORMANCE IN BRAZILIAN SCHOOLS - Elenara Vassanti (CV. Fahr Publishing, 2024)
This study aims to evaluate the impact of Learning Management System (LMS) usage on student academic performance in Brazilian secondary schools. A quantitative descriptive approach was applied to analyze students’ interaction data within LMS platforms and correlate it with their academic grades. Data were collected from 180 students across three public schools using LMS activity logs and online questionnaires. The results revealed a significant positive correlation between LMS usage frequency—especially assignment submissions and discussion forums—and student grade averages. Consistent LMS engagement contributed to improved learning outcomes, particularly when supported by active teacher facilitation and well-integrated digital instructional design. The study recommends enhancing teacher training and digital infrastructure as key strategies to optimize LMS effectiveness in Brazil’s secondary education context.